Nutrition at early stages of life determines the future growth and reproductive performance of beef calves - Philipe Moriel (EDIS)
Metabolic imprinting is the process by which calf nutrition, during first few months of life, may permanently affect the metabolism and performance of beef steers and heifers. Early-exposure to high-concentrate diets may enhance growth performance of beef steers, as well as, enhance the growth performance and accelerate puberty achievement of beef heifers. Identifying strategies that can enhance calf performance during early postnatal life may provide unique opportunities to optimize feed resources and increase the profitability of beef cattle operations.